Can Bank be a Cause of Contagion during the Global Financial Crisis? - Selmi, Nadhem; Hachicha, Nejib (International Journal of Economics and Financial Issues, 2014)
This paper examines whether the bank can be a cause of contagion during the global financial crisis. This paper utilizes a Dynamic Conditional Correlation Model to examine the financial contagion phenomenon following the recent financial crisis. This model, which is already developed by Engle (2002) as a novel specification of multivariate models’ conditional correlations, allows tracking the correlation progress between two assets. Our sample consists of six developed countries, including the American market where the crisis started. Data frequencies are on a weekly basis reflecting between the period January 2006 and December 2011. Overall, the empirical evidence indicates that the past return shocks emanating from the banking sector have a significant impact not only on aggregate stock markets, but also on their prices, suggesting that bank can be a major source of contagion during the crisis. Keywords: Global crisis; International financial contagion; Multivariate GARCH-DCC. JEL Classifications: F3; G14; G21